Esophageal cancer. A prospective phase II study of concomitant-boost external-beam chemoradiation with a top-up endoluminal boost. - Brunner, T; Rupp, A; Melzner, W; Grabenbauer, G; Sauer, R (2008)
PURPOSE: To present the results of a prospective phase II study in esophageal carcinoma. PATIENTS AND METHODS: Patients received single doses of 1.8 Gy up to 27 Gy, then concomitant boost to a total of 50.4 Gy (PTV2 [planning target volume], single dose 1.8 Gy) and 64.8 Gy (PTV1, single dose 1.2 Gy in the morning and 1.8 Gy in the afternoon) concurrently with 800 mg/m(2)/d 5-fluorouracil and 20 mg/m(2)/d cisplatin (weeks 1 and 5). High-dose-rate brachytherapy (2-3 x 6 Gy) on Fridays of weeks 4-6 used a customized applicator facilitating central placement and circumferential dose homogeneity. RESULTS: 50 patients with squamous cell carcinoma (90%) or adenocarcinoma and mostly advanced tumor stage were treated (82% T3/T4 and 70% N1). Median overall survival (median OS 16 months; 1-year-OS 61%; 2-year OS 29%) was significantly longer for patients without nodal disease (35 vs. 11 months; p = 0.01). Hematotoxicity was grade 3 in 11/50, and grade 4 in 1/50 patients. Four percent of higher-grade nausea or vomiting occurred. Esophageal late toxicity was grade 3 in 9/50 patients, and grade 4 in 2/50 patients. CONCLUSION: Survival was excellent especially for patients without nodal disease in this dose-intensified schedule with acceptable tolerability.